FAP-specific signalling is an independent diagnostic approach in ACC and not a surrogate marker of MRI sequences - Liew, Dawn; Röhrich, Manuel; Loi, Lisa; Adeberg, Sebastian; Syed, Mustafa; Gutjahr, Ewgenija; Schlemmer, Heinz-Peter; Giesel, Frederik L.; Bendszus, Martin; Haberkorn, Uwe; Paech, Daniel (Cancers, 2022)
Background: Fibroblast Activation Protein (FAP) is a new target for positron emission tomography and computed tomography (PET/CT) imaging of epithelial tumours embedded in a fibrous stroma. Adenoid cystic carcinomas (ACCs) have shown elevated tracer uptake in 68Gallium (68Ga)-labelled FAPIs in previous studies. The current gold standard for ACC imaging is contrast-enhanced (ce) MRI, where intertumoural heterogeneity leads to variable appearance on T1-weighted (T1w) and T2-weighted (T2w) images. In this retrospective analysis, we correlated 68Ga-FAPI PET signalling at three time points with ceT1w and T2w MRI signals to further characterise the significance of 68Ga-FAPI uptake in ACCs. Methods: Clinical PET/CT scans of 12 ACC patients were performed at 10, 60 and 180 min post i.v. administration of 68Ga-labelled-FAPI tracer molecules. 68Ga-PET- and corresponding MRI-scans were co-registered, and 3D volumetric segmentations were performed on ceT1w and T2w lesions of co-registered MRI slides. Signal intensity values of 68Ga-FAPI PET signalling and ceT1w/T2w MRI scans were analysed for their pixelwise correlation in each patient. Pooled estimates of the correlation coefficients were calculated using the Fisher z-transformation. Results: 68Ga-FAPI PET signals showed a very weak positive correlation with ceT1w values (pooled correlation 0.114, 0.147 and 0.162 at 10, 60 and 180 min) and a weak negative correlation with T2w values (pooled correlation −0.148, −0.121 and −0.225 at 10, 60 and 180 min). Individual r-values at 60 min ranged from −0.130 to 0.434 in ceT1w and from −0.466 to 0.637 in T2w MRI scans. Conclusion: There are only slight correlations between the intensity of 68Ga-FAPI PET signals and tumour appearance in ceT1w or T2w MRI scans, which underlines that 68Ga-FAPI PET signalling is not a surrogate marker of MRI sequences but an independent signal.
Gesehen am 27.10.2022